Characterization of JEN family carboxylate transporters from the acid‐tolerant yeast Pichia kudriavzevii and their applications in succinic acid production - Xi, Yongyan (Microb Biotechnol, 2021)
The unconventional yeast Pichia kudriavzevii is renowned for its ability to survive at low pH and has been exploited for the industrial production of various organic acids, especially succinic acid (SA). However, P. kudriavzevii can also utilize the di‐ and tricarboxylate intermediates of the Krebs cycle as the sole carbon sources for cell growth, which may adversely affect the extracellular accumulation of SA. Because the carboxylic acid transport machinery of P. kudriavzevii remains poorly understood, here, we focused on studying its SA transportation process from the perspective of mining and characterization of dicarboxylate transporters in a newly isolated acid‐tolerant P. kudriavzevii strain CY902. Through genome sequencing and transcriptome analysis, two JEN family carboxylate transporters (PkJEN2‐1 and PkJEN2‐2) were found to be involved in SA transport. Substrate specificity analysis revealed that both PkJEN proteins are active dicarboxylate transporters, that can effectively import succinate, fumarate and L‐malate into the cell. In addition, PkJEN2‐1 can transport α‐ketoglutarate, while PkJEN2‐2 cannot. Since PkJEN2‐1 shows higher transcript abundance than PkJEN2‐2, its role in dicarboxylate transport is more important than PkJEN2‐2. In addition, PKJEN2‐2 is also responsible for the uptake of citrate. To our best knowledge, this is the first study to show that a JEN2 subfamily transporter is involved in tricarboxylate transport in yeast. A combination of model‐based structure analysis and rational mutagenesis further proved that amino acid residues 392‐403 of the tenth transmembrane span (TMS‐X) of PkJEN2‐2 play an important role in determining the specificity of the tricarboxylate substrate. Moreover, these two PkJEN transporters only exhibited inward transport activity for SA, and simultaneous inactivation of both PkJEN transporters reduced the SA influx, resulting in enhanced extracellular accumulation of SA in the late stage of fermentation. This work provides useful information on the mechanism of di‐/tricarboxylic acid utilization in P. kudriavzevii, which will help improve the organic acid production performance of this microbial chassis.